INTRODUCTION - Latest developments in Positive Psychology: The case of Greece - Pezirkianidis, Christos; Stalikas, Anastassios (Psychology: the Journal of the Hellenic Psychological Society, 2020)
In the last two decades, there is a rapid growth of the research initiative on Positive Psychology not only internationally but also in Greece. The present special issue aims at bringing together, highlighting, and promoting research and applications of Positive Psychology in Greece. At first, the authors introduce readers to the history and roots of Positive Psychology and focus on how research on Positive Psychology flourished in Greece. Moreover, emphasis is given on the core concepts of Positive Psychology, namely wellbeing, experiencing positive emotions, psychological resilience, and character strengths. Authors focus on the research conducted in Greece, the psychological instruments that measure them, and the applications of Positive Psychology, e.g. positive education, positive organizations, positive psychotherapy, and positive psychology interventions. To close with, the authors introduce readers to the eleven articles, which are included in the present special issue by presenting their main findings.